Identification of disrupted molecular networks involved in brain maturation and function in the TS1CJE mouse model of down syndrome - Tan, Kai Leng (2016)
Down syndrome (DS) is a chromosomal disorder resulted from trisomy of human chromosome 21 (HSA21). Cognitive impairment is the general feature for all DS individual. To date, there are no answers for the neuropathogenesis in DS individuals which can aid in determining targets for therapeutic interventions. Syntenically conserved HSA21 in mouse chromosome (MMU) 16, MMU17 and MMU10 enabled the generation of DS mouse models with different genetic content for scientific studies. However, insufficient understanding of the neuropathology mechanism in these mouse models impede the effort to unravel the trisomy secret in DS individuals. This study uses Ts1Cje, mouse model of DS with a triplicated region of MMU16 to identify neuropathological mechanisms of defective neurogenesis and neuronal development. We hypothesised that the trisomic genes in MMU16 are over-expressed and disrupts the functional molecular networks, leading to neuropathologies in Ts1Cje mouse brain. In order to prove the hypothesis, transcriptomic analysis comparing Ts1Cje and wild type control on three brain regions (cerebral cortex, cerebellum and hippocampus) across four postnatal (P) time-points (P1, P15, P30 and P84) by using microarray technology to identify the differentially-expressed genes (DEGs) and determination of the potential disrupted molecular network were performed. A total number of 317 DEGs were selected based on a stringent criteria and all the selected trisomic DEGs were up-regulated in their gene expression profiles. Functional clustering analysis of these 317 DEGs showed seven significant pathway clusters including interferon (IFN)- related signalling pathways. Validation of selected DEGs on their gene and protein expression profiles were performed by using quantitative real time polymerase chain reaction (RT-qPCR) and western blotting technique. Results demonstrated overexpression of the trisomic IFN receptor genes [IFN alpha or beta receptor subunit 1 (Ifnar1), IFN alpha or beta receptor subunit 2 (Ifnar2), and IFN gamma subunit 2 (Ifngr2)] and associated DEGs in IFN-induced Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signalling pathway [Leptin receptor (Lepr), and Stat1] on cerebral cortex and cerebellum at P84. Supported by previous study, IFNinduced JAK-STAT signalling pathway is selected to functionally characterise its role in gliogenic shift of DS brains. Preliminary study was conducted with Ifnar1 antagonist treatment on differentiating neural stem cell which was obtained via adult neurosphere culture of Ts1Cje mouse brain. Restoration of defective neurogenesis and neuronal development were determined by RT-qPCR on gene expression profiles of neural stem markers, neuronal markers and glial markers. The result showed that the Ifnar1 antagonist treatment on differentiating neurospheres derived from Ts1Cje was able to revert the aberrant expression of Stat1 to a level that was similar to those derived from wild type control. Collectively, the findings showed the over-expression of IFN receptors particularly Ifnar1 which was due to trisomic segment of MMU16, disrupted IFN-induced JAK-STAT signalling pathway and may also dysregulate the neurogenesis and neuronal development in Ts1Cje mouse brain. Furthermore, the preliminary antagonisation study demonstrated a feasible direction to attenuate neurological abnormalities in DS individuals. This study suggests the potential of IFNinduced JAK-STAT signalling pathway as targets for therapeutic intervention in DS individuals.